2008
DOI: 10.1002/uog.6283
|View full text |Cite
|
Sign up to set email alerts
|

Timing of mid‐trimester cervical length shortening in high‐risk women

Abstract: Objective To examine the natural history of cervical length shortening in women, who had experienced at least one prior spontaneous preterm birth at 17 + 0 – 33 + 6 weeks’ gestation. Methods Analysis of pre-randomization data from the multicenter Vaginal Ultrasound Cerclage Trial. Serial cervical length was measured by vaginal sonography in 1014 high-risk women at 16 + 0 to 22 + 6 weeks. We determined the time (in weeks’ gestation) to cervical length shortening <25 mm, or censoring, either by entering the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 45 publications
(38 reference statements)
1
15
0
Order By: Relevance
“…The data show that cervical length is not normally distributed; in line with the previous observations of Solomon, et al 22 While the cervix appears to have stable length < 24 weeks, there is then a gradual reduction in cervical length of approximately 1mm per week gestation thereafter; these cross‐sectional data are consistent with previous longitudinal assessment, showing a decay rate of 0.5 mm / week gestation 23 . There have been some reports that multiple measures of cervical length may be useful in defining an excessive rate of cervical decay from 16 weeks, that is predictive of preterm labour 24 . Our data, that show wide variation in TA and TV measurement made within individual patients would also suggest that multiple measures would only be of value if assessments were made transvaginally, as the degree of measurement variation seen with the TA approach would mask any objective assessment of cervical decay.…”
Section: Discussionsupporting
confidence: 83%
“…The data show that cervical length is not normally distributed; in line with the previous observations of Solomon, et al 22 While the cervix appears to have stable length < 24 weeks, there is then a gradual reduction in cervical length of approximately 1mm per week gestation thereafter; these cross‐sectional data are consistent with previous longitudinal assessment, showing a decay rate of 0.5 mm / week gestation 23 . There have been some reports that multiple measures of cervical length may be useful in defining an excessive rate of cervical decay from 16 weeks, that is predictive of preterm labour 24 . Our data, that show wide variation in TA and TV measurement made within individual patients would also suggest that multiple measures would only be of value if assessments were made transvaginally, as the degree of measurement variation seen with the TA approach would mask any objective assessment of cervical decay.…”
Section: Discussionsupporting
confidence: 83%
“…26,[29][30][31][32][33][34][35][36][37] Many of these studies, however, evaluated low-risk women 29,30,32,34 or those with symptoms of preterm labor. 37 Several studies have evaluated cervical shortening in high-risk women finding conflicting results, with some suggesting it added additional predictive value, 26,31,33 whereas others found it did not.…”
Section: Discussionmentioning
confidence: 99%
“…26,[29][30][31][32][33][34][35][36][37] Many of these studies, however, evaluated low-risk women 29,30,32,34 or those with symptoms of preterm labor. 37 Several studies have evaluated cervical shortening in high-risk women finding conflicting results, with some suggesting it added additional predictive value, 26,31,33 whereas others found it did not. 35 Shortcomings of previous studies include the fact that many did not evaluate only those identified with a short cervical length, 26,[31][32][33][34] and studies that included only asymptomatic women with singleton gestations found to have a short cervical length did not evaluate other perinatal outcomes apart from preterm birth or gestational age at delivery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations